Justice and Conflict of Interest Quasi Judicial Body – Dental Council in Hong Kong - Cecilia Young (Journal of Medical and Psychological Trauma, 2020)
Dental Councils are Quasi-Judicial Bodies, Declaration of the Conflict of Interest is vital to the fair trial. This short communication discussed the issue regarding the related laws, code of professional ethics and the sample code of conduct for members of public bodies from Independent Commission Against Corruption. A compulsory session for the Declaration of Conflict of Interest is necessary before the Preliminary Investigation and the Hearing.
Keywords: Conflict of Interest